Pengaruh Modal, Tingkat Pendidikan Dan Penggunaan Teknologi Pada Pendapatan UMKM Sektor Perdagangan Di Denpasar Barat - A.A. Sg. Istri Indira Ragapatni; Ni Luh Sari Widhiyani (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research aims to obtain empirical evidence on the effect of capital, education level, and the use of technology on the income of Micro, Small and Medium Enterprises (MSMEs) in the trade sector in West Denpasar. The population of this study is all MSMEs in the trade sector in West Denpasar District with a sample of 99 MSMEs based on the slovin formula. Data collection techniques in the study were carried out by distributing questionnaires with a Likert scale of 1-5. The data analysis technique used in this study is multiple linear regression. The results of the study can prove that the variables of capital, level of education, and use of technology have a positive and significant effect on the income of MSMEs in the trading sector in West Denpasar. The implications of this research are expected to be taken into consideration and input by other MSME actors in increasing income by taking into account capital, education level, and the use of technology. Keyword: MSMEs, capital, education, technology and income